Deprived Urban Neighbourhoods in Poland – Risk of Intergenerational Transmission of Poverty and Social Exclusion - Warzywoda-Kruszyńska, Wielisława; Kruszyński, Kamil (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The paper applies to the problem of child poverty and social deprivation that scholars consider an obstacle for present and future development of society, as it is expressed in the concept of the social investment state. In the article, we discuss the issue in the context of neighbourhood effects approach since growing up in neglected communities is a risk factor for poverty perpetuation in the course of life and across generations. Because the small urban area statistics is unavailable in Poland, we provide results of sociological case study carried out in urban neglected neighbourhoods in Łódź. It enables to present the problem of child poverty through the lens of those affected by disadvantage. The broader context for the discussed problem offer results of analysis based on public statistics concerning dynamics of child poverty and social deprivation in Poland, as compared with other EU member states. Applying interdisciplinary approach, the article aims at getting better understanding of the phenomenon of poverty and social deprivation among children in Poland and its dynamics. We argue that temporal patterns of child poverty and social deprivation may be different in mainstream society approached in research based on representative samples and in poor population living in disadvantaged neighbourhoods. Therefore, we conclude that despite significant decrease in poverty and social deprivation among children, as documented by public statics, Poland is still a country where child poverty is a serious problem and where the grownups located at the bottom of social ladder are “children left behind”.